Observational report: Improved outcomes of transscleral cyclophotocoagulation for glaucoma patients. Issue 23 (June 2017) - Bendel, Rick Edward; Patterson, Michael Ty
Abstract : Abstract: The purpose of this article is to evaluate the improved safety and efficacy of transscleral cyclophotocoagulation (TSCPC) by performing it in the operating room. This is a retrospective review of 17 eyes of 16 patients who received TSCPC for uncontrolled glaucoma on maximum tolerated medication. Mean intraocular pressure (IOP) prior to surgery was 30.85 ± 6.24 mm Hg and was reduced to 14.48 ± 3.53 mm Hg after treatment for an average reduction in IOP of 48.56% at the final visit ( P < .001). Visual acuity was measured at the final follow-up visit and was stable in 13 eyes (76.47%), improved in 2 eyes (11.75%), and decreased in 2 eyes (11.75%). Nine of the eyes (52.94%) saw a reduction in the number of medications taken, whereas 8 had no change. Two eyes had resolved complications of cystoid macular edema (CME) and subconjunctival hemorrhages. The overall success rate is determined to be 88%. TSCPC performed in the operating room may have greater safety and efficacy for patients with uncontrolled glaucoma.